Continuous Flow Deformability‐Based Separation of Circulating Tumor Cells Using Microfluidic Ratchets. Issue 14 (24th February 2016) - Park, Emily S.; Jin, Chao; Guo, Quan; Ang, Richard R.; Duffy, Simon P.; Matthews, Kerryn; Azad, Arun; Abdi, Hamidreza; Todenhöfer, Tilman; Bazov, Jenny; Chi, Kim N.; Black, Peter C.; et al.
Abstract : Circulating tumor cells (CTCs) offer tremendous potential for the detection and characterization of cancer. A key challenge for their isolation and subsequent analysis is the extreme rarity of these cells in circulation. Here, a novel label‐free method is described to enrich viable CTCs directly from whole blood based on their distinct deformability relative to hematological cells. This mechanism leverages the deformation of single cells through tapered micrometer scale constrictions using oscillatory flow in order to generate a ratcheting effect that produces distinct flow paths for CTCs, leukocytes, and erythrocytes. A label‐free separation of circulating tumor cells from whole blood is demonstrated, where target cells can be separated from background cells based on deformability despite their nearly identical size. In doping experiments, this microfluidic device is able to capture >90% of cancer cells from unprocessed whole blood to achieve 10 4 ‐fold enrichment of target cells relative to leukocytes. In patients with metastatic castration‐resistant prostate cancer, where CTCs are not significantly larger than leukocytes, CTCs can be captured based on deformability at 25× greater yield than with the conventional CellSearch system. Finally, the CTCs separated using this approach are collected in suspension and are available for downstream molecular characterization. Abstract : Deformability‐based separation of circulating tumor cells (CTCs) from similarly sized leukocytes using microfluidic ratchets formed by oscillatory flow through asymmetrical constrictions is demonstrated. This mechanism can process whole blood directly to provide divergent paths for CTCs, leukocytes, and erythrocytes depending on cell deformability. In concurrent tests against conventional methods, this system is able to isolate ≈25× more CTCs from patients with castrate resistant prostate cancer.